Pengaruh Pertumbuhan Tabungan, Jumlah Debitur dan Kecukupan Modal Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) di Kecamatan Abang Tahun 2018-2021 - Ni Kadek Dina Yanti; Adiputra, I Made Pradana (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to determine the effect of savings growth, number of debtors and capital adequacy on the profitability of the Village Credit Institution (LPD) in Abang District in 2018-2021. The research design used a mix-method method, namely a combined method consisting of quantitative and qualitative approaches. The number of research samples was 15 LPDs from 20 LPD populations in Abang District. The subject of this research is LPD located in Abang Subdistrict, the sample is determined using purposive sampling technique with certain criteria. Furthermore, for data collection techniques using interviews and collecting secondary data evidence or by looking at the financial statements owned by each LPD. The results of the data collection were then carried out with descriptive statistical tests, classical assumption tests (normality test, multicollinearity test, test of heteroscedasticity), and hypothesis testing (multiple regression analysis), partial significance test (t test) and coefficient of determination test. The research results obtained are that each independent variable has a significant positive effect on the profitability for each LPD in Abang District in 2018-2021.